Integration of Eddy Covariance Fluxes, Tree Ring Records and Stable Isotope Compositions to Study Environmental Controls on Growth in Different-Age Pine Plantation Forests - McKenzie, Shawn (My University, 2019)
Global warming and extreme weather events have impacted the ability of Earth’s forest ecosystems to sequester atmospheric carbon dioxide. The full effects of these events on forest productivity, vulnerability, and the carbon cycle have not yet been fully assessed. One potentially fruitful approach is to explore past climate and forest growth patterns through tree ring records. These records may be used to explore how past environmental events may have impacted tree growth and provide insight into the functioning of forest ecosystems in the future. The stable isotope ratios (e.g. 13C to 12C) of tree ring material also provide additional information about tree growth trajectories and environmental stressors that may not be recognized in radial growth. In this study, tree ring and stable isotope records were measured and constructed to explore the dynamics of growth over the lifespan of plantation pine stands in southern Ontario. Tree ring growth records were used to determine the effects of climate and other environmental changes on radial growth. These records were constructed from two white pine (Pinus strobus L.) plantations established in 1939 (TP39) and 1974 (TP74) and one red pine plantation established in 1931 (TP31). Air temperature, precipitation, and drought indices were analyzed at monthly combinations to determine controls on growth. Temperature was consistently negatively correlated to growth, while precipitation and Palmer Drought Severity Index (PDSI) were consistently positively correlated to growth. The effectiveness of each climate variable to control ring growth differed between sites which may be related to stand age, stand density, and management factors. In both white pine plantations, inter-annual eddy-flux quantifications of gross ecosystem productivity (GEP) was found to be significantly related to tree ring growth over the overlapping period from 2003 to 2017. These relationships enabled an inter-annual estimate of GEP to be constructed for both growth chronologies over the period 1942 to 2017 for TP39 and 1981 to 2017 for TP74). Additionally, growth rings from three specimens in two different-age (14- and 77-year old) white pine plantation forests were analyzed for stable carbon isotope ratios to identify both short- and long-term variations in the physiological response to changing environmental conditions. Variations in δ13C time series from whole wood samples provided a potential record of intrinsic water use efficiency (iWUE) for these three trees. These iWUE records were compared to climate records and inter-annual eddy-flux quantifications of GEP and evapotranspiration (ET). Long-term iWUE was found to increase by 50 μmol mol–1 yr–1, with nearly all of the increase occurring as the tree shifted into active homeostasis of stomatal control in the late 1960s. Changes in time series of internal and external concentration of CO2 (ratio) also displayed a significant shift from first increasing and then decreasing trend. In the three wood samples, air temperature, ET, and GEP were found to be significantly, but inconsistently related to iWUE. The work of this thesis shows that tree ring properties are strongly related to key environmental variables such as temperature and drought stress in pine plantation forests in southern Ontario, Canada. Results also suggest that dendrochronology and isotope tracers are useful tools to be used to evaluate historical environmental impacts on growth in these different-age plantation stands. The background knowledge of climate drivers acting on tree ring growth and ring isotopic compositions over the forests’ history may be used to make informed management decisions to promote tree productivity in a changing climate in Eastern North America.
Environmental Controls on Growth in Different-Age Pine Plantation Forests
Keywords: forest; biogeosciences; tree ring; eddy covariance; carbon isotopes; southern Ontario